ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA SOAL SETARA INSTRUMEN TIMSS UNTUK SISWA SMP NEGERI 1 MASOHI - Hikmawati, Andi; Laurens, Theresia; Wattimanela, Henry J (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
Mathematical problem solving ability is one of the abilities that must be mastered by students in order to be able to mathematically solve problems often found in real life. The purpose of this study was to describe students' mathematical problem solving abilities on the volume of cubes and blocks equivalent to the TIMSS instrument. The research subjects are five students of class IX science at SMP Negeri 1 Masohi who were selected based on the category of problem solving ability. This type of research is a qualitative descriptive research supported by quantitative data. The data obtained from this study is data on mathematical problem solving ability tests such as written tests and interviews. The results show that students with very high abilities are able to interpret problems well, interpret strategies and problem-solving steps accaording to the plan, and consistently check back. Students with high abilities are able to apply the four steps in solving ploblems even though there are some questions that students make mistakes in setting strategies and substituting scores at the completion stage. Students with moderate abilities sometimes make mistakes in setting a strategy, make calculation errors, and do not check back to the maximum so that they get inaccurate results. Meanwhile students with low abilities unable to meet the completeness of the stage of understand the problem is writing down the things that are known and asked. As for students with low abilities cannot solve problems completely because of poor planning. Making mistakes in calculations and not checking again so that they do not get the right results